2018
DOI: 10.1002/chem.201800616
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic Hydroxylation of Sterols by Steroid C25 Dehydrogenase from Sterolibacterium denitrificans

Abstract: The electrochemically driven catalysis of the complex molybdoenzyme steroid C25 dehydrogenase (S25DH) from the β-Proteobacterium Sterolibacterium denitrificans is reported. S25DH catalyses the oxygen-independent regioselective hydroxylation of the tertiary C25 atom of sterols and also their derivatives. Cholest-4-en-3-one is a native substrate for S25DH, which produces 25-hydroxycholest-4-en-3-one as a product of catalytic turnover. Cholecalciferol (vitD ) is also a substrate. S25DH was immobilised on a modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
(57 reference statements)
0
3
0
Order By: Relevance
“…Warnke et al reported a more than threefold higher V max for VD3 (1.48 nmol/min/mg) compared to that obtained for the 3-hydroxy steroid 7-dehydrocholesterol (0.47 nmol/min/mg) (Warnke et al 2016 ). Recently, the apparent K M values were determined in an electrochemical system yielding K M = 740 μM for cholest-4-en-3-one and K M = 327 μM for VD3 (Kalimuthu et al 2018 ). The advent of overexpression system for S25DH in T. aromatic K172 allowed kinetic characterization of individual enzymes.…”
Section: O 2 -Independent Hydroxylationmentioning
confidence: 99%
See 2 more Smart Citations
“…Warnke et al reported a more than threefold higher V max for VD3 (1.48 nmol/min/mg) compared to that obtained for the 3-hydroxy steroid 7-dehydrocholesterol (0.47 nmol/min/mg) (Warnke et al 2016 ). Recently, the apparent K M values were determined in an electrochemical system yielding K M = 740 μM for cholest-4-en-3-one and K M = 327 μM for VD3 (Kalimuthu et al 2018 ). The advent of overexpression system for S25DH in T. aromatic K172 allowed kinetic characterization of individual enzymes.…”
Section: O 2 -Independent Hydroxylationmentioning
confidence: 99%
“…The proposed system was also applied for hydroxylation of various 3-ketosteroids such as: cholest-4-en-3-one, cholest-1,4-dien-3-one and cholest-4,6-dien-3-one with a final concentration in the range of 2.2 g/L, or sterols such as: cholesterol, 7-dehydrocholesterol, with a final concentration in the range of 0.8 g/L (Rugor et al 2017a ). Purified S25DH was also efficiently immobilized on silica (Rugor et al 2017a ) or on a microfiltration membrane (Kalimuthu et al 2018 ). In both cases, the enzymatic reaction was coupled to an electrochemical system, which turned out to be sensitive to changes in substrate concentration.…”
Section: O 2 -Independent Hydroxylationmentioning
confidence: 99%
See 1 more Smart Citation